ANALYSIS OF THE EFFECTIVENESS OF PERFORMANCE ASSESSMENT STRATEGIES IN INCREASING EMPLOYEE PRODUCTIVITY IN INDOMARET BEKASI CITY - Sumarsid, Sumarsid (Yayasan Education and Social Center, 2025)
This research aims to analyze the effectiveness of performance appraisal strategies in increasing employee productivity at Indomaret, Bekasi City. This research was conducted in January 2025, using a qualitative approach and data collection through interviews, observation and documentation. The research results show that the performance assessment strategy implemented at Indomaret focuses more on quantitative measures such as sales targets. While this approach provides clear metrics for performance, it ignores important qualitative aspects such as customer service, teamwork, and employee engagement. This research also shows that feedback given to employees tends to be evaluative rather than constructive, which negatively impacts overall motivation and productivity. In addition, the use of technology for real-time performance monitoring has been proven to increase the transparency and accuracy of assessments. However, communication regarding the purpose and benefits of performance appraisal is lacking, which reduces its effectiveness. Based on these findings, this research recommends improvements in the feedback process, the inclusion of qualitative performance indicators, and increased communication about the purpose and benefits of performance appraisals to create a more productive work environment at Indomaret, Bekasi City.